Gopro Wangi Effectiveness: Presenting Market Opportunities For Banyuwangi Umkm - Yannira Elda Saharani; Adi Suhendra; Daisy Marthina Rosyanti (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
This study evaluates the implementation of the GOPRO WANGI program, an initiative of the Banyuwangi Regency Government that aims to improve the accessibility of promotional facilities for Micro, Small, and Medium Enterprises (MSMEs) through the provision of free promotional carts. The program is expected to support the visibility of MSMEs, strengthen local competitiveness, and empower the economy of local communities. Despite its positive impact on improving market access, the program faces several challenges in terms of management, maintenance, and transparency of the selection process. This research uses a descriptive qualitative approach through interviews, observations, and document studies to identify issues related to the program and find solutions that can improve its effectiveness. The results show that the sustainability of the program requires improvements in terms of cart availability, training for MSME participants, as well as periodic evaluations to ensure long-term benefits for the development of MSMEs in Banyuwangi.